ST3GAL1 is a target of the SOX2-GLI1 transcriptional complex and promotes melanoma metastasis through AXL - Silvia Pietrobono (Nature Portfolio, 2020)
Understanding the molecular events controlling melanoma progression are necessary to find improved therapeutics. Here, the authors report oncogenic SOX2-GLI1 transcriptional complex to drive melanoma invasion through the induction of the sialyltransferase ST3GAL1, and report ST3GAL1-AXL axis as driver of melanoma metastasis.